Tourism, travel and tweets: algorithmic text analysis methodologies in tourism. (1st January 2013) - Claster, William; Pardo, Phillip; Cooper, Malcolm; Tajeddini, Kayhan
Tourism and hospitality organisations depend on market knowledge to compete in innovation, product development, and customer relationship management. This paper shows that new forms of social media provide valuable and previously difficult to obtain real-time knowledge on tourist perceptions, concerns, and sentiment towards tourist destinations – both those already visited and those under consideration for a future visit. We show how analysis of comments from such social media as Twitter micro-blogs can be used to reveal potential and recent tourists motivations in the travel and hospitality industry in various locations.